Should the government sell you goods? Evidence from the milk market in Mexico - Diego Jiménez Hernández; Enrique Seira (Federal Reserve Bank of Chicago, 2023)
Governments spend considerable resources providing goods directly. We show that such behavior may increase welfare when private suppliers have market power. We do this by studying the staggered rollout of hundreds of government milk "ration stores" in Mexico using a proprietary panel of household food purchases. The rollout lowered the price per liter of privately supplied milk by 2.4% and increased household consumption. To compare direct provision with budget-neutral alternatives, we develop and estimate an equilibrium model of the market that accounts for quality differences. Direct provision generates larger consumer surplus than milk vouchers and unrestricted cash transfers.
Keywords: H42; L33; L44; L66; O15; 330; private and public provision; market concentration; milk